Religion and culture in the discourse of the European Court of Human Rights: the risks of stereotyping and naturalising. Issue 2 (1st May 2014) - Peroni, Lourdes
Abstract This paper critically examines the ways in which the European Court of Human Rights represents applicants' religious and cultural practices in its legal discourse. Borrowing tools from critical discourse analysis and incorporating insights from the anti-essentialist critique, the paper suggests that the Court has most problematically depicted the practices of Muslim women, Sikhs and Roma Gypsies. The analysis reveals that, by means of a reifying language, the Court oftentimes equates these groups' practices with negative stereotypes or posits them as the group's 'paradigmatic' practice / way of life. The thrust of the argument is that these sorts of representation are problematic because of the exclusionary and inegalitarian dangers they carry both for the applicants and for their groups. In negatively stereotyping applicants' practices and in privileging certain group practices over others, these types of assessment underestimate what is at stake for the applicants and potentially exclude them from protection. Moreover, these types of reasoning risk sustaining hierarchies across and within groups. The paper concludes by sketching out an approach capable of mitigating stereotyping and essentialising risks.